Impact of U.S. Overseas Schools in Latin America onValues - John J. Ketterer; George E. Marsh (Arizona State University, 2001)
This study focuses on the attitudinal outcomes of schooling in American Overseas Schools in Latin America with respect to democracy and citizenship, the formation of views about the United States, and student attitudes about the American international school.